1988
DOI: 10.1002/1097-0142(19880515)61:10<2083::aid-cncr2820611025>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic prognostic factors in adenocarcinomas of the peripheral lung less than 2 CM in diameter

Abstract: The histologic prognostic factors of pulmonary adenocarcinomas of the lung less than 2 cm in diameter were analyzed in 75 patients who had undergone surgical resection. The pathologic stage, lymph node involvement, and pleural involvement were found to be the major determinants of prognosis (P less than 0.01). In addition, other single factors, such as tumor differentiation (P less than 0.01), vascular invasion (P less than 0.01), the degree of collagenization in the fibrotic focus (P less than 0.01), the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
1
6

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(76 citation statements)
references
References 20 publications
8
61
1
6
Order By: Relevance
“…The precise mechanism underlying the worse OS with the T/T genotype being associated with p53 status remains unknown [32]. However, tumors of MDM2 T/T patients tended to be positive in LVI and pleural invasion (Table 3), which have been reported to be worse prognostic factors associated with tumor proliferation and aggressiveness [33,34]. These results indicate that the tumors of T/T patients in the stage I period might have overall malignant potential, although p53 tumor suppressor function is normal.…”
Section: Mdm2 Snp309 and Lung Cancer Prognosessupporting
confidence: 92%
“…The precise mechanism underlying the worse OS with the T/T genotype being associated with p53 status remains unknown [32]. However, tumors of MDM2 T/T patients tended to be positive in LVI and pleural invasion (Table 3), which have been reported to be worse prognostic factors associated with tumor proliferation and aggressiveness [33,34]. These results indicate that the tumors of T/T patients in the stage I period might have overall malignant potential, although p53 tumor suppressor function is normal.…”
Section: Mdm2 Snp309 and Lung Cancer Prognosessupporting
confidence: 92%
“…The prognosis of lung cancer correlates with histopathological type and differentiation (Takise et al 1988). The development and progression of carcinoma is thought to follow a series pathological type, clinical features and patient prognosis after resection.…”
mentioning
confidence: 98%
“…Previous studies had reported that several pathological factors were related to survival rate; these factors include visceral pleural invasion, [19][20][21][22] vascular invasion, [23] perineural invasion, [24][25][26] histologic grade, [27] and nuclear atypia. [28] Our multivariate analysis indicated that only perineural invasion had a significant effect on disease-free and overall survival rates among N2 NSCLC patients. Perineural invasion was defined as cancer cell spreading to the space surrounding a nerve and was confirmed by the pathologist.…”
Section: Discussionmentioning
confidence: 99%